Different responses of soybean cultivars to potassium - Rossetto, Claudia A. V.; Fernandes, Dirceu M.; Ishimura, Issao; Rosolem, Ciro A. (Pesquisa Agropecuaria Brasileira, 1995)
Soybean (Glycine max (L.) Merrill) is known to have a high ability as a potassium extractor, and different cultivars show different potassium requirements. An experiment was run to study the potassium nutrition of soybean as related to plant characteristics. Six soybean cultivars (FT-2, Bossier, IAC-11, IAC-17, IAC-18 and IAC-19) were grown in 6 kg pots filled with the topsoil of a Dark Red Latosol (sandy loam), either with and without K fertilization. The plants were harvested 70 days after emergence. Soybean response to potassium was not related to growth habit or group of maturation. There was a different response to K. The cultivars IAC-18 and FT-2 were less tolerant to K deficiency. Potassium deficiency in the leaves was not related to top dry matter production. With K fertilization soybean plants showed small root volume and higher ratio canopy/root. With high K in soil, all of the cultivars showed higher nodulation.